Friction and Wear Behavior of Wear-Resistant Belts in Drill Joints for Deep and Ultra-Deep Wells - Zhang, K.; Wang, Z.Q.; Wang, D.G. (Проблемы прочности, 2018)
The friction and wear of an new material for the drill joint were compared with those of traditional wear-resistant belt materials using an SD-1 test rig against a 42Mn2V steel counterface under deep and ultra-deep well conditions. This provides recommendations as to the tribological application of the wear-resistant belt. The results obtained strongly indicate that the friction and wear of a polycrystalline diamond (PCD) composite are much lower than those of the traditional wear-resistant belt materials. Among those materials, the friction and wear behavior of a FeNiNb alloy are higher than those of a FeCrMnMo alloy. Of the three wear-resistant belt materials, the bilateral protection performance of a PCD composite is the best one. It is feasible to use this composite as the wear-resistant belt material in the drill joint for deep and ultra-deep wells. The dominant wear mechanism of the wear-resistant belt materials is the microcutting wear, accompanied by the adhesive one. In addition, the wear degree of the PCD composite is the least one.